Economics of rivalry, conflict and cooperation - Gangopadhyay, Partha (World Scientific Pub. Co., 2011)
This book offers an extensive and original study of the dynamics of rivalry, evolution of costly and violent conflicts, and potential cooperation among powerful players. It unravels the special features of the global socio-economic system that can make it extremely fragile and vulnerable. It serves as a good reference source for anyone interested in some of the pressing and emerging problems of the global system, such as intra-national and interethnic conflicts, climate change challenges, poverty and terrorism, and provides useful and rigorous insights into the collective bid to resolve some of these problems. Written in a simple and accessible manner, this book will help researchers and policy makers in understanding and abetting costly conflicts